2019
DOI: 10.3390/md17110630
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Lipid Components from 15 Species of Tropical and Temperate Seaweeds

Abstract: The present study describes the variation in lipid components from 15 species of seaweeds belonging to the Chlorophyta, Ochrophyta, and Rhodophyta phyla collected in tropical (Indonesia) and temperate (Japan) areas. Analyses were performed of multiple components, including chlorophylls, carotenoids, n-3 and n-6 polyunsaturated fatty acids (PUFAs), and alpha tocopherol (α-Toc). Chlorophyll (Chl) and carotenoid contents varied among phyla, but not with the sampling location. Chl a and b were the major chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 93 publications
2
24
1
4
Order By: Relevance
“…Among the species of macroalgae studied in the articles of this special issue, we find, for example, the species harvested in Indonesia and Japan, where lipid content variations were evaluated. Susanto et al (2019) [10] concluded that the total lipid (TL) content and fatty acid composition were strongly affected by sampling location. The TL and n-3 PUFA levels tended to be higher in temperate seaweeds compared to those in tropical seaweeds.…”
Section: Algae As Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the species of macroalgae studied in the articles of this special issue, we find, for example, the species harvested in Indonesia and Japan, where lipid content variations were evaluated. Susanto et al (2019) [10] concluded that the total lipid (TL) content and fatty acid composition were strongly affected by sampling location. The TL and n-3 PUFA levels tended to be higher in temperate seaweeds compared to those in tropical seaweeds.…”
Section: Algae As Foodmentioning
confidence: 99%
“…The TL and n-3 PUFA levels tended to be higher in temperate seaweeds compared to those in tropical seaweeds. In this study were analyzed four species of edible green algae (Chlorophyta; edible seaweeds of the world): Caulerpa lentillifera and Ulva reticulata, harvested in Indonesia; Ulva intestinalis, U. australis, and U. reticulata, harvested in Japan; five species of red algae (Rhodophyta): Gracilariopsis longissima, harvested in Indonesia, Gloiopeltis furcata, Chondrus yendoi, Mazzaella japonica and Chondria crassicaulis, harvested in Japan; and six species of brown algae (Ochrophyta, Phaeophyceae): Sargassum aquifolium, harvested in Indonesia, Costaria costata, Undaria pinnatifida, Saccharina japonica, Sargassum fusiforme and S. horneri, harvested in Japan [5,10].…”
Section: Algae As Foodmentioning
confidence: 99%
“…Hence the DNA barcodes of G. salicornia generated in the present study will be useful for exploring invasive potential and in macroalgal identification during microbial-macro-algal interaction studies. Gracilariopsis longissima are actively cultured seafood (Bermejo et al, 2020) and a source of bioactive compounds (Susanto et al, 2019). Hydropuntia edulis were known for its high content of UV-absorbing compounds (Tanaka et al, 2020).…”
Section: Dna Barcoding Rhodophyta and Its Utilitymentioning
confidence: 99%
“…Jenis karotenoid yang dominan terdapat dalam Sargassum sp. adalah fukosantin (Fs) (Susanto et al 2016, Susanto et al 2019. Sedangkan senyawa fenol merupakan metabolit sekunder berbentuk cincin benzen aromatik yang memiliki satu atau lebih gugus hidroksil yang terikat langsung dengan cincin aromatik, termasuk turunan fungsionalnya.…”
Section: Pendahuluanunclassified
“…Karotenoid merupakan pigmen yang larut dalam lemak sehingga senyawa ini dapat terekstrak dalam pelarut organik metanol (Park et al 2007). Rumput laut cokelat mengandung beberapa jenis karotenoid antara lain zeaksantin (Zs), violasantin (vs), beta-karoten (β-kar), dan Fs (Susanto et al 2019). Karotenoid pada ekstrak metanol S. duplicatum mengalami degradasi selama penyimpanan suhu ruang yang terpapar sinar matahari ( Figure 2).…”
Section: Hasil Dan Pembahasan Perubahan Karotenoid Selama Penyimpananunclassified